2012
DOI: 10.1166/msr.2012.1007
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular and Intercellular Traffic of NAD<SUP>+</SUP>, NAD<SUP>+</SUP> Precursors and NAD<SUP>+</SUP>-Derived Signal Metabolites and Second Messengers: Old and New Topological Paradoxes

Abstract: NAD + metabolism and regulation are still incompletely defined in their features. Specifically, several compartmentation problems, both subcellular and intercellular, have emerged in the past years. A topological paradox was identified in the CD38/NAD + /Cyclic ADP-ribose system which represents a means for achieving regulation of intracellular Calcium levels ([Ca 2+ ] i and of Ca 2+ -mediated cell functions. CD38, an ectoenzyme featuring ADP-ribosyl cyclase (ADPRC) activity, is known to catalyze the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…A vesicular mechanism has been proposed, positing that CD38 can be endocytosed, together with transport proteins, into endolysosomes. The transporters can then mediate the influx of substrates for CD38 and efflux of cADPR from the endolysosomes to act on the endoplasmic Ca 2+ stores (14,15). Recently, we have shown that CD38, in fact, can exist in two opposite membrane orientations, not only in the expected type II orientation but also in the opposite type III orientation, with the catalytic C-domain facing the cytosol (16).…”
Section: Junmentioning
confidence: 99%
“…A vesicular mechanism has been proposed, positing that CD38 can be endocytosed, together with transport proteins, into endolysosomes. The transporters can then mediate the influx of substrates for CD38 and efflux of cADPR from the endolysosomes to act on the endoplasmic Ca 2+ stores (14,15). Recently, we have shown that CD38, in fact, can exist in two opposite membrane orientations, not only in the expected type II orientation but also in the opposite type III orientation, with the catalytic C-domain facing the cytosol (16).…”
Section: Junmentioning
confidence: 99%
“…Thus, an astrocyte-to-neuron calcium signal can be triggered in such cells by the CD38/cADPR system, which, through the activation of (Verderio et al, 2001). Further, co-culture of either cortical or hippocampal astrocytes with neurons results in a significant over-expression of astrocytic CD38, both on the plasma membrane and intracellularly, and revealed a new neuron-to-astrocyte glutamatergic signaling based on the CD38/cADPR system; this affects [Ca 2+ ] i in both cell types, adding further complexity to the bi-directional patterns of communication between astrocytes and neurons (Bruzzone et al, 2012;2004). Not only in cultured astrocytes but also in astrocytes in situ, the expression of CD38 and a second messenger triggering Ca 2+ release from intracellular stores, either cADPR (Banerjee et al, 2008) or NAADP + (Heidemann et al, 2005), has been observed.…”
Section: Discussionmentioning
confidence: 98%
“…We have shown that secretion of OT is dependent on Ca 2+ amplification through ryanodine receptors sensitive to cyclic ADP-ribose (cADPR) (Bruzzone et al, 2012;Lee, 2012), while that of AVP is not Jin et al, 2007;Liu et al, 2008;Liu et al, 2012). Although the precise mechanism for this discrepancy is not clear, the simplest explanation for this may be the differential expression of CD38 in OT or AVP neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key enzyme responsible for synthesis of cADPR is ADP-ribosyl cyclase (Lee et al, 1997, 2012a andHigashida, et al, 1997 and2012a andDe Flora et al, 2004;Podesta et al, 2005;Bruzzone et al, 2012). Intriguingly, this enzyme shows a high degree of identity to the mammalian T cell surface marker CD38 (Takasawa et al, 1993;Malavasi et al, 2008;Lee, 2012a).…”
Section: Introductionmentioning
confidence: 99%